Application Of Control Functions In Efforts To Slow The Cpo Process (Crude Palm Oil) At The Ptp Palm Factory. Nusantara Vi Ophir Business Unit: Penerapan Fungsi Kontrol Dalam Upaya Memperlambat Proses Cpo (Crude Palm Oil) Di Pabrik Sawit Ptp. Unit Bisnis Nusantara Vi Ophir - Septi Eirlangga, Yofhanda (Journal of Community Service and Application of Science, 2024)
The main problem of this PKM concerns the implementation of the control function in an effort to increase the smooth running of CPO at PT's palm oil mill. Perkebunan Nusantara VI Ophir Business Unit. This research is expected to have an impact on the company, which will serve as a basis for solving the problem of improving the CPO production process so that the company's goals can be achieved optimally. Seeing the existing problems, the solution that can be given to PT. Perkebunan Nusantara VI Ophir Business Unit is to create a master production schedule first in a comprehensive production plan, and also by utilizing science and technology, which is much more advanced at this time. Free fatty acids are an indicator of the quality of oil; the higher the free fatty acids in the oil, the worse the quality of the oil. For this reason, efforts need to be made to prevent the formation of free fatty acids in oil, so that the company standard of a maximum free fatty acid content of 4.8% is achieved. Companies should improve K3 supervision so that workers do not experience work accidents in the CPO processing process, and companies must supervise the sorting implementation so that the types of fruit that come in are of good quality and quality